Maternal gestational vitamin D supplementation and offspring bone health (MAVIDOS): a multicentre, double-blind, randomised placebo-controlled trial - Cooper, C; Harvey, N; Bishop, N; Kennedy, S; Papageorghiou, A; Schoenmakers, I; Fraser, R; Gandhi, S; Carr, A; D'Angelo, S; Crozier, S; Moon, R; et al. (Elsevier, 2016)
Background: Maternal vitamin D status has been associated with bone mass of offspring in many, but not all, observational studies. However, maternal vitamin D repletion during pregnancy has not yet been proven to improve offspring bone mass in a randomised controlled trial. We aimed to assess whether neonates born to mothers supplemented with vitamin D during pregnancy have greater whole-body bone mineral content (BMC) at birth than those of mothers who had not received supplementation. Methods: The Maternal Vitamin D Osteoporosis Study (MAVIDOS) was a multicentre, double-blind, randomised, placebo-controlled trial that recruited pregnant women from three study sites in the UK (Southampton, Oxford, and Sheffield). Eligible participants were older than 18 years, with a singleton pregnancy, gestation of less than 17 weeks, and a serum 25-hydroxyvitamin D (25[OH]D) concentration of 25-100 nmol/L at 10-17 weeks' gestation. P'articipants were randomly assigned (1:1), in randomly permuted blocks of ten, to either cholecalciferol 1000 IU/day or matched placebo, taken orally, from 14 weeks' gestation (or as soon as possible before 17 weeks' gestation if recruited later) until delivery. Participants and the research team were masked to treatment allocation. The primary outcome was neonatal whole-body BMC, assessed within 2 weeks of birth by dual-energy x-ray absorptiometry (DXA), analysed in all randomly assigned neonates who had a usable DXA scan. Safety outcomes were assessed in all randomly assigned participants. This trial is registered with the International Standard Randomised Controlled Trial registry, ISRCTN 82927713, and the European Clinical Trials Database, EudraCT 2007-001716-23. Findings: Between Oct 10, 2008, and Feb 11, 2014, we randomly assigned 569 pregnant women to placebo and 565 to cholecalciferol 1000 IU/day. 370 (65%) neonates in the placebo group and 367 (65%) neonates in the cholecalciferol group had a usable DXA scan and were analysed for the primary endpoint. Neonatal whole-body BMC of infants born to mothers assigned to cholecalciferol 1000 IU/day did not significantly differ from that of infants born to mothers assigned to placebo (61·6 g [95% CI 60·3-62·8] vs 60·5 g [59·3-61·7], respectively; p=0·21). We noted no significant differences in safety outcomes, apart from a greater proportion of women in the placebo group with severe post-partum haemorrhage than those in the cholecalciferol group (96 [17%] of 569 mothers in the placebo group vs 65 [12%] of 565 mothers in the cholecalciferol group; p=0·01). No adverse events were deemed to be treatment related. Interpretation: Supplementation of women with cholecalciferol 1000 IU/day during pregnancy did not lead to increased offspring whole-body BMC compared with placebo, but did show that 1000 IU of cholecalciferol daily is sufficient to ensure that most pregnant women are vitamin D replete, and it is safe. These findings support current approaches to vitamin D supplementation in pregnancy. Results of the ongoing MAVIDOS childhood follow-up study are awaited.